ANALISIS LITERASI KEUANGAN TERHADAP KEBERLANGSUNGAN UMKM DENGAN INKLUSI KEUANGAN PADA UMKM GIANYAR - Yuliyawati Yuliyawati; Mardiana Mardiana (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2023)
The UMKM sector is a component of trading tools, but in order to achieve an increase in the quantity of UMKM, reforms must be carried out to support the sustainability of UMKM by conveying knowledge about financial literacy and financial inclusion. The purpose of this study is to evaluate and describe the impact of financial literacy on the sustainable development of small, medium and micro enterprises through inclusive finance as an intervention variable. The research location is Gianyar Regency, Bali. The research sample applied a purposive sampling technique and solvency formula, and the samples obtained were 85 samples. This research utilizes primary and secondary data. Questionnaires are used as a data collection method. SmartPLS (Partial Least Squares) is the data analysis process used. The results of the study stated that financial literacy has a significant effect on the sustainability of MSMEs, financial literacy has a significant effect on financial inclusion, financial inclusion has a significant effect on the sustainability of MSMEs and financial inclusion is not an intervening variable on the effect of financial literacy on the sustainability of MSMEs.